Descriptive Data Analysis Examining How Standardized Assessments Are Used to Guide Post–Acute Discharge Recommendations for Rehabilitation Services After Stroke. Issue 5 (1st May 2015) - Bland, Marghuretta D.; Whitson, Michelle; Harris, Hilary; Edmiaston, Jeff; Connor, Lisa Tabor; Fucetola, Robert; Carter, Alexandre; Corbetta, Maurizio; Lang, Catherine E.
Abstract : Background: Use of standardized assessments in acute rehabilitation is continuing to grow, a key objective being to assist clinicians in determining services needed postdischarge. Objective: The purpose of this study was to examine how standardized assessment scores from initial acute care physical therapist and occupational therapist evaluations contribute to discharge recommendations for poststroke rehabilitation services. Design>: A descriptive analysis was conducted. Methods: A total of 2, 738 records of patients admitted to an acute care hospital with a diagnosis of stroke or transient ischemic attack were identified. Participants received an initial physical therapist and occupational therapist evaluation with standardized assessments and a discharge recommendation of home with no services, home with services, inpatient rehabilitation facility (IRF), or skilled nursing facility (SNF). A K-means clustering algorithm determined if it was feasible to categorize participants into the 4 groups based on their assessment scores. These results were compared with the physical therapist and occupational therapist discharge recommendations to determine if assessment scores guided postacute care recommendations. Results: Participants could be separated into 4 clusters (A, B, C, and D) based on assessment scores. Cluster A was the least impaired, followed by clusters B, C, and D. In cluster A, 50% of the participants were recommended for discharge to home without services, whereas 1% were recommended for discharge to an SNF. Clusters B, C, and D each had a large proportion of individuals recommended for discharge to an IRF (74%–80%). There was a difference in percentage of recommendations across the clusters that was largely driven by the differences between cluster A and clusters B, C, and D. Limitations: Additional unknown factors may have influenced the discharge recommendations. Conclusions: Participants poststroke can be classified into meaningful groups based on assessment scores from their initial physical therapist and occupational therapist evaluations. These assessment scores, in part, guide poststroke acute care discharge recommendations.